A Study of the Scientific Literacy Profile of Prospective Biology Teachers in Papua - Hanida Listiani; Ruth Megawati; Suriyah Satar; Cartika Candra Ledoh; Nurbaya Nurbaya (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
21st-century education requires teachers to master various skills in order to face the challenges of globalization, one of which is scientific literacy skills. This study aims to describe the scientific literacy profile of Biology Education students at Cenderawasih University as prospective Biology teachers in Papua. The research was conducted from June to July 2025. A quantitative method with a descriptive approach was employed. The sample consisted of 48 students selected using a convenience sampling technique. The instrument used was the Test of Scientific Literacy Skills (TOSLS). The data were analyzed descriptively through percentage calculations and categorization of scientific literacy levels. The results showed that, overall, the students’ scientific literacy abilities fall into the low category. These findings indicate the need for strategies to improve scientific literacy through innovative learning, strengthening inquiry-based activities, and utilizing contextual digital learning resources. This research is expected to serve as a foundation for the development of scientific literacy enhancement programs within the Biology Education Department at Cenderawasih University.